THE DIVISION OF INHERITANCE BETWEEN UNILATERAL AND BILATERAL SIBLINGS (REMUNOM, 2024)
This study focuses on how to deal with inheritance and post-inheritance sharing inequalities between unilateral and bilateral siblings. Article 1,841 of the Civil Code treats them unequally and, because of this imposed distinction, there is a theoretical difference in the constitutionality of this article. Civil legislation distinguishes unilateral brothers and bilateral brothers based on hereditary order. For example, in the Civil Code of 1916, unilateral brothers are influenced by bilateral brothers, which violates the principle of equality in the Constitution. Filiation and inheritance law in Brazil have followed a long and winding path, shaped by social, legal and doctrinal transformations. From Portuguese colonization to the 1988 Federal Constitution and the current Civil Code, family relationships and the transmission of assets have undergone profound changes. Filiation was marked by inequalities, with a clear distinction between legitimate, natural and adopted children. Succession law reflected this reality, giving priority to legitimate children in inheritance. The 1988 Magna Carta, however, enshrined the principle of equality, recognizing the same rights and duties for all children, regardless of the form of parentage. The Civil Code, in turn, established legitimate succession, where the deceased's assets are divided among their descendants, spouse and other family members. Although the rules seek equality between siblings, doctrine and jurisprudence recognize the need to consider other criteria, such as the need for and collaboration with family assets, to guarantee social justice in succession. The trajectory of filiation and inheritance law in Brazil demonstrates the constant search for a fairer and more equitable system, where the principles of equality and human dignity are fully respected. Understanding this complex history is fundamental to building a future where family relationships and the transmission of goods are guided by justice and solidarity. The 1988 Constitution includes equality before the law as one of its principles. Based on the principle of family equality, equality between children is also guaranteed. In the issue of inheritance between siblings, the Civil Code stipulates a larger portion for the division of inheritance between siblings, which harms the interests of the siblings because the law does not resolve this issue.